The Evolution of the Appendectomy: From Open to Laparoscopic to Single Incision - Noah J. Switzer; Richdeep S. Gill; Shahzeer Karmali (Scientifica)
Beginning with its initial description by Fitz in the 19th century, acute appendicitis has been a significant long-standing medical challenge; today it remains the most common gastrointestinal emergency in adults. Already in 1894, McBurney advocated for the surgical removal of the inflamed appendix and is credited with the initial description of an Open Appendectomy (OA). With the introduction of minimally invasive surgery, this classic approach evolved into a procedure with multiple, smaller incisions; a technique termed Laparoscopic Appendectomy (LA). There is much literature describing the advantages of this newer approach. To name a few, patients have significantly less wound infections, reduced pain, and a reduction in ileus compared with the OA. In the past few years, Single Incision Laparoscopic Appendectomy (SILA) has gained popularity as the next major evolutionary advancement in the removal of the appendix. Described as a pioneer in the era of “scarless surgery,” it involves only one transumbilical incision. Patients are postulated to have reduced post-operative complications such as infection, hernias, and hematomas, as well as a quicker recovery time and less post-operative pain scores, in comparison to its predecessors. In this review, we explore the advancement of the appendectomy from open to laparoscopic to single incision.